Coating of Tin Octoate on Ceramic Support as A Function of Concentration and Sintering Temperature - Ibrahim, Norliza; Husna Kamarulzam, Siti; Mohd Adnan, Nurasmida; Nadzirah Suhaidi, Amira (International Journal of Engineering and Technology, 2018)
Tin octoate was used as condensation polymerization catalyst in the production of polylactic acid (PLA). As the phase of catalyst was similar to PLA as product and lactide as reactant, this caused difficulty in recycling the catalyst and contaminant of PLA product if the catalyst remained in the product solution. Therefore, this study aimed to prepare heterogeneous catalyst by depositing tin octoate onto ceramic support using sol-gel method.Â  Effects of concentration of tin octoate and sintering temperature of the coated layer were studied. The concentrations of catalyst used in preparing the coating solution were 250 ppm, 500 ppm and 750 ppm, while the temperatures were ranged from 150oC to 250oC. The coated layer was characterized by adhesion and Energy Dispersive X- ray (EDX) test. The result showed that ceramic support coated with 500 ppm of tin octoate solution had the highest distribution of tin and the strongest adhesion compared to the other two. While for the temperature, it had been shown that sintering temperature at 150oC produced high quality of coating as the percentage area removed was only 5%. However, temperature at 200 oC presented the highest amount of tin which was 11.97%. In conclusion, good heterogeneous catalyst in terms of catalyst distribution and its attachment on ceramic support was able to be produced using 500 ppm of tin octoate at sintering temperature of 200 oC.Â Â